Stories of Agency in the Lives of Incarcerated Women - Carolyn Sandoval; Lisa M Baumgartner (Adult Education Research Conference, 2016)
Researchers explored the role of agency in the lives of women offenders. Life history interviews were conducted with 13 women. Five themes emerged including (1) resourcefulness, (2) self-protection, (3) getting even, (4) resisting gendered expectations and (5) resisting stigma and valuing self. Findings have implications for educators and helping professionals.
Keywords: incarcerated women; life history; narrative analysis